Preventive Medicine And "Mission Civilisatrice" Uses Of The Bcg Vaccine In French Colonial Vietnam Between The Two World Wars - Monnais, Laurence (Penerbit Universiti Sains Malaysia (USM Press), 2006)
This paper is part of a broader analysis of French health policy in colonial Vietnam1 (1860–1945), and in particular of the campaigns organized in the region by the French administration against the most important epidemic and endemic diseases, during a key period in the history not only of the emergence of biomedicine and its principal preventive strategies, but also of state intervention into public health issues in Europe and in the West in general. The fight against tuberculosis, one of the most deadly local endemic diseases, is a very revealing example of the contents, complexity and ambiguity of French health policy in Vietnam. Probing the decision to use the Bacille Calmette-Guérin (BCG) vaccine in the 1920s will be particularly helpful for better understanding the function of public health in the colonizing process and in the relationship between colonizer and colonized. The use of BCG in Vietnam, which was both early and extensive in comparison with its use in France as we will see, seems likely to provide us with important new ways of understanding the role of the colonial empire in driving scientific experimentation and "progress", in particular by revealing the colonial administration's autonomy from metropolitan imperialist directives which, when not absent, were often not responding to local needs